Strategi Komunikasi Kepemimpinan Ketua KPSDM dalam Membangun Motivasi Kerja untuk Meningkatkan Kinerja Karyawan di Hotel S Jakarta - Naila Refalina Alaya Anastasya; Clarisa Dwinanda Febriani (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
Leadership communication strategies are essential for fostering employee motivation and improving organizational performance. This study aims to analyze the leadership communication strategy implemented by the Head of KPSDM in enhancing employee motivation and performance at Hotel S Jakarta. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews and documentation, with the Head of KPSDM serving as the key informant. Data validity was ensured through source triangulation, while analysis involved data reduction, data display, and conclusion drawing. The findings reveal that the Head of KPSDM applies communication strategies through regular meetings, direct and online communication, continuous monitoring, and performance evaluation. Communication functions not only to deliver information but also to strengthen coordination, supervision, and work control. Furthermore, employee motivation is enhanced through guidance, constructive feedback, problem-solving support, and appreciation for successfully completed tasks. Continuous evaluation and reward systems also contribute to improving employee discipline, teamwork, and the achievement of organizational targets. The study concludes that effective leadership communication significantly strengthens work motivation and supports improved employee performance, highlighting its strategic role in achieving organizational objectives and maintaining sustainable organizational effectiveness.